Draft Cross-Cultural Communication in the Perspective of the Quran and its Application in Dynamics Communication Practical - Erlan Gantira; Widia Ningsih (International Journal of Social Research, 2025)
Study This discuss draft communication cross culture in perspective of the Qur'an, especially based on QS. Al-Hujurat verse 13, and its implementation in dynamics communication modern professional. The verse confirm that man created in diversity tribes, nations, and cultures to be mutual getting to know (ta'aruf), as well as put piety as size main glory human. Research This use method literature or study literature with approach qualitative descriptive from perspective communication cross culture and interpretation of the Koran. Study results show that mark introduction own relevance strong with the concept of intercultural competence which emphasizes importance openness, empathy, respect, and ability adapt in interaction intercultural. In addition, the verse This reject ethnocentrism and encourage attitude ethnorelativism in communication. Implementation principles the seen in various field communication professionals, such as marketing communication, corporate communication, communication management, and broadcasting. In practice, understanding to background behind culture audience become factor important in develop effective, inclusive, and non-invasive communication strategies discriminatory. Research this also confirms that communication based on mark piety will produce deeper relationship fair, dignified, and harmonious. With Thus, QS. Al-Hujurat verse 13 no only own spiritual dimension, but also become runway ethical and normative in build communication cross culture in the era of globalization. Values the relevant For create communication professionals who appreciate diversity and strengthening Work The same between individuals and group in public multicultural.